Asas Kepatutan (Billijkheid) Pemerintah Indonesia dalam Mendukung Two State Solution antara Palestina dan Israel - Muhammad Dzulfikar Syaiful Ali (Juridische : Jurnal Penelitian Hukum, 2024)
This writing aims to legal reconstruction of the paradigm and direction of international legal policy, especially related to the two state solution between Israel and Palestine. The method used is a normative research method with a conceptual approach and a historical approach. The principle of decency is a virtue that encourages humans to will and act rationally based on the concept of justice. Appropriateness is an excuse for not implementing an unjust law (equity contra legem). The establishment of Israel began with the Balfour Declaration from 1923 to 1948 which caused Britain to make a political promise to the Zionist movement in the form of a Jewish Homeland. United Nations (UN) Resolution No. 181 is an illegal decision. This is because the resolution is outside the authority (ultra vires) of the UN General Assembly and this is against absolute norms (jus cogens), namely the right to self-determination (right to self-determination). The Government of the Republic of Indonesia must comply with the provisions of the Preamble to the 1945 Constitution that in fact independence is the right of all nations and therefore, colonialism in the world must be abolished because it is not in accordance with humanity and justice. The solution that should be emphasized by the Government of the Republic of Indonesia is a referendum for the Palestinian people to determine the fate of their own nation. A Palestinian people's referendum can be a juridical basis for complete Palestinian independence. Accepting or supporting a two state solution is a betrayal of the constitutional mandate and an oppressed nation like Palestine. However, justice can only be upheld not by accepting colonial entities and land grabbers as a state, but rather through defending colonized and oppressed peoples.